The Characteristics of Ahmad Tohari's Smile Short Story by Ahmad Tohari - Ahmad Khoiril Anam; Yogi Purnama (Universitas Indraprasta PGRI, 2021)
The purpose of this study is to describe the characters contained in the collection of short stories Senyum Karyamin by Ahmad Tohari. The method used in this research is qualitative descriptive research. The research technique used is the analysis of the contents of collection of short stories and literature studies to find and collect library data in the form of books relating to research sebjects. Research on the characterization of the main characters in a collection of short stories with the use of analytical and dramatic aspects of the story of thirteen sub-chapters. The results found the chacarterization of the main characters in a short stories with use of analytical aspects of 53 findings (51%) and dramatic 51 findings (49%) that appear in the story of thirteen sub-chapters that exist. Short collection of Senyum Karyamin depicts the character of rural communities that reflect daily life.Keywords: Main Character, Analytical Aspects, Dramatic Aspects, Short Stories Senyum Karyamin.